3D Modeling and Motion Simulation of Multi-ridge Globoid Cam in ATC based on Pro/E - Cao Peng; Ge Zhenghao; Liu Xiaoqin (Jixie chuandong)
Currently,it is difficult to set up an accurate model for the multi- ridge globoid cam with complex curved surface in automatic tool changer（ ATC）. Taking the geometric theory in globoidal cam as basis,the contour surfaces program of each roller in different movement period are written according to the meshing situation between the driven plate roller and the globoidal cam. And then the curves are merged and the contour surfaces are obtained by using curve and surface function in Pro / E. The normal offsets of theoretical contour surfaces are conducted,and a new accurate cam solid model is obtained. At last,the virtual prototype of the globoidal cam mechanism is built by using ADAMS,through the motion simulation and analysis,the accuracy of the model is verified.